Myanmar's 'Rohingya' conflict - Ware, Anthony, 1966-; Laoutides, Costas (C. Hurst & Co. (Publishers) Ltd., 2018)
Exploring the long-running tripartite conflict between the Rohingya, Rakhine and Burman ethnic groups, this book offers a new analysis of the complexities of the conflict: the fears and motivations driving it and the competition to control historical representations and collective memory